The relationship between self-esteem and self-concept clarity is modulated by spontaneous activities of the dACC - Chen, Yujie; Liu, Yanchi; Gao, Yuan; Wu, Xin; Mo, Lei (Frontiers in Psychology, 2022)
Although it has been found that self-esteem and self-concept clarity are positively correlated, self-determination theory shows that the positive relationship might be lowered for individuals whose basic psychological needs are chronically thwarted. The exact neural mechanisms underlying the relationship between self-esteem and self-concept clarity are still not fully understood. The dorsal anterior cingulate cortex (dACC) plays an important role in monitoring basic psychological needs, considering that it is more active when some basic psychological needs are actually or potentially thwarted. To better understand the neural mechanisms underlying the relationship between self-esteem and self-concept clarity, we investigated the differences in the relationship between self-esteem and self-concept clarity among healthy adults with different levels of spontaneous activities of the dACC using rs-fMRI combined with amplitude of low-frequency fluctuation (ALFF). As expected, the results showed that the positive relationship between self-esteem and self-concept clarity was modulated by the ALFF value of the right dACC, which indicated that the positive relationship was significant when the ALLF value of the right dACC was lower, but the positive relationship was not significant when the ALFF value of the right dACC was higher. The modulating roles of right dACC might also reflect that the individuals with higher ALFF value of dACC might experience chronically thwarted relatedness of basic psychological needs, which means the more disturbed by thwarting relatedness information in individuals, the lower positive relationship emerged.